The Geographical Interpretation of the Diffusion of the Information Technology Engineer Knowledge - Éva Bakota Pósfai; Pósfainé Bakota Éva (II. Rákóczi Ferenc Kárpátaljai Magyar Főiskola-Valerij Padjak, 2013)
Abstract. In this article, our aim is to present the innovative educational activity of a tertiary educational institution, the Dennis Gabor College, being in certain aspects an isolated spot and situated in an isolated location within the institutional system of the Hungarian higher education, by using the research methods of geography. Namely, how its new “educational idea”, the establishment (invention) and realisation (innovation) of the information technology engineer and computer economist bachelorlevel coursesin open- and distance education forms became available for the whole society and economy.

A cikkben arra vállalkozom a geográfia kutatási eszközeit és módszerét felhasználva, hogy bemutassam a magyar felsőoktatás intézményrendszerén belül, annak bizonyos értelemben elszigetelt pontjaként értelmezhető és helyszínéhez köthető felsőoktatási intézmény, a Gábor Dénes Főiskola oktatás innovációs tevékenységét. Nevezetesen, hogy az új „oktatási ötletének” a műszaki informatikus és a gazdasági informatikus alapképzési szakok nyitott és távoktatási képzési formában történő (invenció) megszületése, majd megvalósulása (innováció) miként válhatott a társadalom, a gazdaság egésze számára hozzáférhetővé.
Географічна інтерпретація поширення знань інформаційних технологій інженерії
https://opac3.brff.monguz.hu:443/hu/record/-/record/157029
https://www.kmf.uz.ua/hun114/letoltes/acta/ActaAcBereg2013_2.pdf
Keywords: Geographical Interpretation; Information Technology Engineer Knowledge; distance education